2018
DOI: 10.1002/mrm.27473
|View full text |Cite
|
Sign up to set email alerts
|

Brain active transmembrane water cycling measured by MR is associated with neuronal activity

Abstract: These results suggest that AWC is associated with neuronal activity and NKA activity is a major contributor in coupling AWC to neuronal activity. Although AWC comprises steady-state, homeostatic transmembrane water exchange, our analysis also yields a simultaneous measure of the average cell volume, which reports any slower net transmembrane water transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 61 publications
0
39
0
1
Order By: Relevance
“…Results indicate that we have developed a non-invasive, sufficiently rapid method of measuring exchange across membranes in live tissue. The AXR ≈ 100 s −1 is significantly faster than intracellular-extracellular water exchange rates measured in neural tissue (≈ 0.5 − 5 s −1 ) (42,(89)(90)(91)(92). Such fast turnovers are not unheard of, e.g.…”
Section: Discussionmentioning
confidence: 87%
“…Results indicate that we have developed a non-invasive, sufficiently rapid method of measuring exchange across membranes in live tissue. The AXR ≈ 100 s −1 is significantly faster than intracellular-extracellular water exchange rates measured in neural tissue (≈ 0.5 − 5 s −1 ) (42,(89)(90)(91)(92). Such fast turnovers are not unheard of, e.g.…”
Section: Discussionmentioning
confidence: 87%
“…tive transmembrane water exchange)可能是功能磁共振 能检测神经元活动的机制 [161] . 此外, 麻省理工学院的 研究人员设计出了一种基于磁共振成像的钙活性成像 方法 [162] , 该方法可以跟踪活体动物神经元内的信号传 导过程, 能够将神经活动与特定行为联系起来.…”
Section: 近期 国内开展的一项新的研究表明 跨膜水交换(Ac-unclassified
“…It was previously thought k io = k io (p): there was no active component. However, this is not the case: k io (a) is always present, and often dominant . It is elaborated as (x/([H 2 O i ]〈V〉)) c MR NKA , where c MR NKA is the cellular metabolic rate of the cell membrane Na + ,K + ‐ATPase (NKA) (fmol(ATP)hydrolyzed/cell/s), [H 2 O i ] is the intracellular water concentration, and x is the stoichiometric mole ratio of water actively cycled to ATP hydrolyzed by NKA [fmol(H 2 O)/fmol(ATP)].…”
Section: Introductionmentioning
confidence: 99%
“…This is important because NKA can be considered biology’s most vital enzyme, but its in vivo homeostatic activity has never been measurable or amenable to mapping . Significantly, it has been found that k io correlates with metastatic potential in breast and melanoma cell lines, and with neuronal firing in brain tissue . This is a new imaging biomarker with potentially great power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation